Reply to Curtis, L. Comment on "Magner et al. Sulforaphane Treatment in Children with Autism: A Prospective Randomized Double-Blind Study. Nutrients 2023, 15, 718" - Magner, Martin; Švandová, Ivana; Houška, Milan (Nutrients, 2024)
We thank Dr. Curtis for his interest and feedback [...].